PENGARUH BIAYA LINGKUNGAN, CSR DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI INTERVENING - Antonetha Maharani Lololau; Paulina Yuritha Amtiran; Filipus Argentano Guntur Suryaputra (UNIVERSITAS DHARMAWANGSA, 2026)
The mining sector makes a significant contribution to Indonesia’s economy however, environmental risks and fluctuations in firm value remain ongoing concerns. This study aims to examine the effect of environmental costs, Corporate Social Responsibility (CSR), and firm size on firm value, with profitability as an intervening variable, in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research employed a quantitative approach using panel data regression analysis with EViews 12. The sampling technique used purposive sampling, resulting in 10 companies with a total of 50 observations. The analysis included descriptive statistics, model selection tests, classical assumption tests, t-tests, the coefficient of determination, and the Sobel Test. The results indicate that environmental costs do not have a significant effect on profitability but have a positive and significant effect on firm value. CSR has no significant effect on either profitability or firm value. Firm size does not significantly affect profitability but has a negative and significant effect on firm value. Profitability has a positive and significant effect on firm value. Furthermore, profitability is unable to mediate the effects of environmental costs, CSR, and firm size on firm value. These findings suggest that the disclosure of environmental costs and improved profitability serve as positive signals to investors, while larger asset ownership is perceived as a sign of inefficiency in the mining sector.